A Comparative Analysis of the Agile and Traditional Software Development Processes Productivity - de Souza Carvalho, W. C.; Rosa, P. F.; dos Santos Soares, Michel; Teixeira da Cunha Junior, Marco Antonio; Buiatte, L. C. (2011 30th International Conference of the Chilean Computer Science Society, 2011)
Software development processes are essential for an organization to obtain the required levels of productivity and quality. The productivity analysis of agile and traditional development processes is an open and few explored research area, which has attracted the interest of industrial and academic fellows in order to take advantage of the strengths of both approaches. This research aims to investigate good options for agile and traditional integration by defining a hybrid process that takes advantage of both approaches. An empirical study aiming to evaluate the productivity impact of the proposed hybrid process was carried out in a Brazilian CMMI v.1.1 Maturity Level 2 medium-sized company. Five groups of similar projects were compared with respect to productivity, some of which were developed using the new hybrid process and others were developed using the older RUP-based process. Quantitative results have shown that four out of five project groups showed significant productivity increase in Scrum-RUP projects. The study shows that it is possible to integrate agile practices in the software development process without losing the rigor needed in the desired sub processes and still get real development productivity gain.